Uraemic symptom burden and clinical condition in women and men of ≥65 years of age with advanced chronic kidney disease: results from the EQUAL study. Issue 7 (13th June 2018) - van de Luijtgaarden, Moniek W M; Caskey, Fergus J; Wanner, Christoph; Chesnaye, Nicholas C; Postorino, Maurizio; Janmaat, Cynthia J; Rao, Anirudh; Torino, Claudia; Klinger, Marian; Drechsler, Christiane; Heimburger, Olof; Szymczak, Maciej; et al.
Abstract: Background: The epidemiology and prognosis of chronic kidney disease (CKD) differ by sex. We aimed to compare symptom prevalence and the clinical state in women and men of ≥65 years of age with advanced CKD receiving routine nephrology care. Methods: The European QUALity study on treatment in advanced chronic kidney disease (EQUAL) study follows patients from six European countries of ≥65 years of age years whose estimated glomerular filtration rate (eGFR) dropped to ≤20 mL/min/1.73 m 2 for the first time during the last 6 months. The Dialysis Symptom Index was used to assess the prevalence and severity of 33 uraemic symptoms. Data on the clinical state at baseline were collected from medical records. Prevalence was standardized using the age distribution of women as the reference. Results: The results in women ( n = 512) and men ( n = 967) did not differ with age (77.0 versus 75.7 years) or eGFR (19.0 versus 18.5). The median number of symptoms was 14 [interquartile range (IQR) 9–19] in women, and 11 (IQR 7–16) in men. Women most frequently reported fatigue 39% [95% confidence interval (CI) 34–45] and bone/joint pain [37% (95% CI 32–42)] as severe symptoms, whereas more men reported difficulty in becoming sexually aroused [32% (95% CI 28–35)] and a decreased interest in sex [31% (95% CI 28–35)]. Anaemia [73% (95% CI 69–77) versus 85% (95% CI 82–87)] was less common in women than in men, as were smoking history and cardiovascular comorbidity. However, a diagnosis of liver disease other than cirrhosis, psychiatric disease and mild malnutrition were more common among women. Conclusions: Women in secondary care with an incident eGFR ≤20 mL/min/1.73 m 2 reported a higher symptom burden, while their clinical state was considered similar or even more favourable as compared with men.